Rediseño de la red de campus de la Casa Inspectorial Salesiana del Ecuador ubicada en la ciudad de Quito, sector el Girón - López Ramos, María Cristina (2015)
The project is the redesign of the network for the Salesian Provincial House of Ecuador, allowing this to be the matrix that is located in the city of Quito to communicate with their branches that are located throughout Ecuador. By integrating voice, data and video network enables companies to largely cover communication needs.